A conceptual market framework for water-bound nitrate pollution. Issue 2 (4th March 2018) - Broadbent, Craig D.; Bernknopf, Richard L.; Brookshire, David S.
Abstract: The conversion of bottomland hardwood and swamp forests to irrigated agriculture has had problematic consequences for water bodies. Many of these problems can be linked to the use of synthetic nitrogen fertilizers to increase crop production. To date, there is little monitoring of nitrogen use in watersheds, which may be due to large fixed costs. Using market-based techniques which have addressed previous environmental challenges, with remotely sensed data to track a pollutant's source, may be one alternative, by incentivizing nitrogen users to behave according to abatement costs traced back to the point of origin of a pollutant.